2018
DOI: 10.1111/bjhp.12344
|View full text |Cite
|
Sign up to set email alerts
|

‘What if I'm not dead?’ – Myth‐busting and organ donation

Abstract: Objectives In the United Kingdom, three people die every day awaiting an organ transplant. To address this, Scotland and England plan to follow Wales and introduce opt‐out donor consent. However, emotional barriers, myths, and misconceptions may deter potential registrants. Our objectives were to estimate the number of people who plan to opt‐out of the donor register and to test whether emotional barriers (e.g., medical mistrust) differentiated participants within this group. Finally, in an experimental manipu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 18 publications
1
44
2
2
Order By: Relevance
“…In recognition of this, NHS Blood and Transplant (NHSBT) currently provides a ‘myth‐busting’ feature on their webpage as a method of dispelling myths and correcting misinformation surrounding organ donation: https://www.organdonation.nhs.uk/helping-you-to-decide/about-organ-donation/myths-about-organ-donation/. Recent work has examined the impact of this campaign on self‐reported organ donor intentions (Miller et al , ). The study found that dispelling harmful organ donation myths increased intentions for those with favourable attitudes towards organ donation, namely participants who plan to actively opt‐in to the register and those who plan to follow deemed consent when opt‐out legislation is introduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recognition of this, NHS Blood and Transplant (NHSBT) currently provides a ‘myth‐busting’ feature on their webpage as a method of dispelling myths and correcting misinformation surrounding organ donation: https://www.organdonation.nhs.uk/helping-you-to-decide/about-organ-donation/myths-about-organ-donation/. Recent work has examined the impact of this campaign on self‐reported organ donor intentions (Miller et al , ). The study found that dispelling harmful organ donation myths increased intentions for those with favourable attitudes towards organ donation, namely participants who plan to actively opt‐in to the register and those who plan to follow deemed consent when opt‐out legislation is introduced.…”
Section: Discussionmentioning
confidence: 99%
“…Given the relatively novel nature of opt‐out consent legislation in the United Kingdom, few studies have investigated the factors deterring donors under these laws. Although recent research has shown that emotional barriers are significantly heightened for individuals who signal an intention to opt‐out, this study utilized a quantitative measure of emotional barriers, which may limit the depth of understanding into these complex emotive factors (Miller, Currie, & O'Carroll, ). Ultimately, obtaining a rich and nuanced understanding of these factors using qualitative methodology, from a prospective point of view, may enable researchers to identify modifiable barriers that could be targeted before the introduction of opt‐out consent.…”
Section: Introductionmentioning
confidence: 99%
“…"Myth-Busting": Myths or incorrect beliefs (e.g., "Doctors may not try their best to save my life if I am registered as an organ donor") are common deterrents of organ donation registration. Miller, Currie and O'Carroll (2018) recently evaluated the effectiveness of myth correcting interventions. They found that for participants who plan to opt-in to the organ donor register or passively register (deemed consent), dispelling myths acted to increase donor intentions.…”
Section: Blood and Organ Donation 42mentioning
confidence: 99%
“…This is critical, as extensive research has shown emotional beliefs and attitudes, for example, discomfort at thinking about one’s death, to be key determinants of donor behaviour in countries with opt-in legislation [911]. Recent work has also confirmed negative emotional beliefs to be heightened for participants who plan to opt-out of the donor register if deemed consent laws are introduced in Scotland and England [12].…”
Section: Introductionmentioning
confidence: 99%